Research on movement and deposition of snow particles with different shapes in the bogie region. (May 2023) - Lan, Hong; Cai, Lu; Zhang, Jiye; He, Peiheng
Natural snow particles come in various complex shapes and have different forces acting on them. The forces acting on snow particles of various shapes are customised in this study based on the shape correction coefficients and sphericity theories. The wind and snow flow at the bottom of the train are solved by coupling the unsteady Reynolds-averaged Navier–Stokes simulation with the discrete phase model to explore the snow accumulation problem of high-speed train bogies more realistically. The findings reveal that changing the morphology of snow particles impacts their resistance to movement in the bogie region, affecting their mobility in the bogie region. Snow particles with higher resistance will stay in the low-speed zone of the bogie region, increasing snow particle concentration and accumulation, whereas snow particles with lower resistance follow airflow movement and gather fewer in the low-speed zone. Different shapes of snow particles accumulate in different amounts on the bogie components, with the most accumulation by spherical snow particles in the braking system and suspension system surface. Therefore, using spherical snow particles to simulate wind and snow flow phenomenon at the bottom of the train can indicate the worst case.